2020
DOI: 10.3390/v12101086
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Transmission of Naked Viruses through Extracellular Vesicles: Focus on Polyomaviruses

Abstract: Extracellular vesicles have recently emerged as a novel mode of viral transmission exploited by naked viruses to exit host cells through a nonlytic pathway. Extracellular vesicles can allow multiple viral particles to collectively traffic in and out of cells, thus enhancing the viral fitness and diversifying the transmission routes while evading the immune system. This has been shown for several RNA viruses that belong to the Picornaviridae, Hepeviridae, Reoviridae, and Caliciviridae families; however, recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The more cytopathic effect associated to GLV HP infection could be explained by an impaired release of viral particles that remain trapped inside the parasite, accumulating faster than they are released. Alternative strategies for virions egress has been described for non-enveloped naked viruses hijacking different types of extracellular vesicles, such as microvesicles (MVs), secretory autophagosomes and exosomes for nonlytic release [70][71][72]. The tight association of GLV particles with MVs outside of the cell might suggest GLV can exploit the MVs budding mechanism or stimulate MV budding.…”
Section: Discussionmentioning
confidence: 99%
“…The more cytopathic effect associated to GLV HP infection could be explained by an impaired release of viral particles that remain trapped inside the parasite, accumulating faster than they are released. Alternative strategies for virions egress has been described for non-enveloped naked viruses hijacking different types of extracellular vesicles, such as microvesicles (MVs), secretory autophagosomes and exosomes for nonlytic release [70][71][72]. The tight association of GLV particles with MVs outside of the cell might suggest GLV can exploit the MVs budding mechanism or stimulate MV budding.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was also found in the fungus C. fructicola , which was infected by a Hadaka virus, CfRV1, where many irregular large vesicles possessing small vesicles appeared inside the virus-infected fungus, as observed by TEM ( 33 ). Some large vesicles that could be fused with the cellular plasmalemma seem to be important components of endocytosis used by other naked viruses ( 32 , 56 ). In our study, endocytosis of the CaPV1-infected strain was indeed seriously affected, as observed by FM4-64 dye staining.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses such as norovirus, [ 136 ] rhinovirus, [ 137 ] hepatitis A (HAV) [ 137 ] and E virus, [ 137 ] enterovirus 71, [ 138,139 ] rotavirus, [ 136 ] or poliovirus, [ 140,141 ] among others, are capable of exploiting different cellular mechanisms for the production of EVs containing viral components, which have been recently explored in an excellent review. [ 142 ] The association of the viruses with EVs confers a series of advantages for their propagation, such as their release through a nonlytic pathway and, thus, the preservation of the infected virus‐producing cell; the masking of the viral proteins from the neutralizing antibodies of the host organism; or the possibility of propagation through a wider range of transmission routes. [ 143,144 ] Interestingly, EVs not only confer advantages during virus trafficking through the organism but are also heavily involved in the entry of EV‐associated virions to new host cells.…”
Section: Viral Penetrationmentioning
confidence: 99%